The theater of His glory nature and the natural order in the thought of John Calvin - Schreiner, Susan E. (Grand Rapids, MI Baker Academic, 1991)
Includes bibliographical references and indexes.
Keywords: Calvin, John, -- 1509-1564; Nature -- theology